Online Vehicle Licensing Adoption as Public Service Innovation for Better Public Transportation in Surakarta - Rino Ardhian Nugroho; Galang Restu Gusti Morajaela; Septyanto Galan Prakoso; Purwati Retno Wulandari (Universitas Padjadjaran, 2023)
Transportation becomes the most essential part of a country's development. As a matter of fact, in 2018 The Online Land Transportation and Multimodal Licensing System (SPIONAM) was launched by The Indonesia Ministry of Transportation. The main purpose of this application is to facilitate business licensing in land transportation. The most intriguing of this study is that there is no relevant research dealing with the elements that influence user acceptance of SPIONAM. In other words, there are no prominent records regarding user's reactions to this application. This study examined the acceptance of SPIONAM in Surakarta. Besides using qualitative methods, this study utilized the UMEGA (Unified Model of Electronic Government Adoption) theory as well. Interviews were conducted as a method to collect data. The findings indicated that some aspects affect the application of SPIONAM in Surakarta. The aspects are expected benefits, expected convenience, social influence, facility conditions, perceived risk, user attitudes, and user interests. The study also discovers that the UMEGA model applies to qualitative research with several alignments.